Z_k-stratifolds (2018)
The present work brings together two important theories given by the Zk-manifolds from Sullivan and stratifolds from Kreck. We introduce the bordism theory of Zk-stratifolds in order to solve Steenrod?s problem for Zk-coefficients in an affirmative way. Finally, we present a geometric interpretation of the Bockstein long exact sequence and the Atiyah-Hirzebruch spectral sequence for Zk-bordism (k odd).